PS49 Food For Thought! The Role Of Dietary Choices On Cognitive Behaviour. (17th September 2012) - Cadar, D; Pikhart, H; Mishra, G; Stephen, AM; Kuh, D; Richards, M
Abstract : Background: Cognitive decline indicates the first sign of dementia and a major public health impact associated with ageing. Evidence suggests that dietary patterns are associated with cerebrovascular and cardiovascular risk factors. Methods: To examine the association between dietary choices and 20 years cognitive decline from 43 to 60+.; 1018 study members from the MRC National Survey of Health and Development regularly followed up since birth in 1946 were included in the study. Cognitive functioning was measured at 43 and 60+ years using two tests: verbal memory (maximum words recalled 45) and visual search (maximum letter searched: 600). Dietary data was obtained using a 5 days diet diary at age 36 and 43y. An overall score representing level of healthy food choice was derived, by summing scores from five separate criteria: 1. consumption of breakfast (0 no consumption to 2 all days); 2.type of milk (from 0 whole to 3 skim milk); 3. type of bread (from 0 white to 4 wholemeal); 4. number of daily portions of fruit and vegetables (from 0 none to 5 portions/day) and percentages of energy from daily intakes (0-more than 45% energy to 5 -less than 30% energy). A total score was derived and further classified as 0 low or 1 higher choice, subject to median split at each age. A cumulative midlife score was further derived as 0 low choice at either age or 1 higher choice at least at one age or both. The confounding variables were father's social class, childhood cognition, education, adult social class and depression. Results: There was a cross sectional positive association between a higher choice of diet and verbal memory scores at age 43y compared to a lower choice 1.83 (95% CI 1.12 to 2.54). This association was maintained after adjusting for all covariates. There was also a significant association between a midlife cumulative healthier choice of diet and a slower verbal memory from 43 to 60+ in a fully adjusted model 0.69 (1.10 to 1.27) compared to midlife lower choice. There was no association between dietary choice and visual search or visual search decline. Conclusion: Our results suggest that a healthy dietary option based on high intake of fruit and vegetables, complex carbohydrates and cereals made in early midlife is protective of verbal memory decline from mid to later life. Public health interventions based on healthy diets and the prevention of nutritional deficiencies should be considered an important line of defence against cognitive decline and dementia.